A Study on Motivational Levels of Teachers in Lhuentse District, Bhutan - Drukpa, Gyeltshen (International Journal of Humanities and Education Development (IJHED), 2021)
Many stakeholders in the country describe poor performance of learners is attributed to motivational level of teachers. Principal plays an important role in motivating teacher. This study focuses on factors that impact teachers’ motivation in Lhuentse District of Bhutan and on the role of Principal in enhancing teachers’ motivation.Many initiatives have been taken at the Ministry, Department, District and School levels to improve the learning outcomes of students. Tremendous work has been done to achieve a holistic development of the children by infusing the four pillars of Gross National Happiness (GNH), the eight dimensions and seventy-two indicators into the school curriculum. Enormous amount of money and time has been invested for the professional Development programs for the teachers. Principal in school are now seen to take a major role than just a mere administrator. Therefore, qualitative research has further conducted to find out some of the challenges that demoralize teachers professionally and to identify factors that contribute on motivation of teachers in the schools of the District.